The branching architecture of artemisia ordosica and its resistance to wind erosion - Qu, Zhiqiang; Li, Zhiguo; Hu, Linxi; Liu, Lianyou; Hu, Xia; Zhang, Guoming; Lv, Yanli; Guo, Lanlan; Yang, Yanyan; Yang, Ziqiong; Han, Guodong (Frontiers in Environmental Science, 2022)
Different branching architectures reflect the adaptation strategies of different plants and affect their resistance to wind erosion. This study presents field-based observations that demonstrate the relationship between the branching architecture of Artemisia ordosica and its resistance to wind erosion. This species is the dominant plant species in the semi-fixed and fixed dunes of the Mu Us Sandland. The research found that bifurcation ratio, ratio of branch diameter and fractal dimension of branching were greater in semi-fixed sandland than in fixed sandland. The aerodynamic roughness was greaterin the A. ordosica community in the fixed and semi-fixed sandland than in the bare sandland. The airflow fields in the cross-wind direction were strongly affected by the windward shape of the plants, which became gradually narrower from the base to the top, while in the leeward direction, the wind speed at different heights behind the plant returned to the incoming airflow velocity. This result confirms that the influence of the windward shape of the plant on the surrounding airflow field is much larger than the influence of plant thickness, porosity or other factors.